In silico and in vivo anti-inflammatory studies of curcuminoids, turmeric extract with zinc oxide, and eugenol - Asti Meizarini (Pharmacotherapy Group, Faculty of Pharmacy, University of Benin, 2018)
Purpose: To determine the anti-inflammatory activity of curcuminoids in comparison with that of eugenol in silico, and to determine the anti-inflammatory activity of wound dressings made from zinc oxide powder and liquid turmeric extract with a high curcuminoid content. Methods: In silico studies were conducted, using Molegro Virtual Docker program, to predict the antiinflammatory potency of curcuminoids (curcumin, demethoxycurcumin, bisdemethoxycurcumin) and eugenol against COX-2 receptors. In vivo studies to evaluate anti-inflammatory activity via TNFα expression, were carried out using thirty Wistar rats as subjects, divided into two groups: A (sacrificed on day 3) and B (sacrificed on day 7). Each group contained three subgroups (n = 5): A1, B1 were excised without a dressing as control subgroups; A2, B2 were excised followed by the application of zinc oxide with a turmeric extract dressing; and A3, B3 were excised followed by the application of zinc oxide with an eugenol dressing. Results: The in silico studies confirmed the anti-inflammatory activity of curcumin (-132.905 kcal/mol), demethoxycurcumin (-130.265 kcal/mol), bisdemethoxycurcumin (-118.827 kcal/mol) in relation to the COX-2 receptor to be greater than that of eugenol (-78.718 kcal/mol). The in vivo studies of TNFα expression showed that the levels of activity in the groups without dressings were significantly higher than in those with dressing (p<0.05), while the lowest TNFα expression were for zinc oxide with turmeric extract dressings. Conclusion: The combination of zinc oxide with turmeric liquid extract has a higher anti-inflammatory effect than eugenol as demonstrated by both in vivo and in silico studies. This combination can, therefore, be used as an alternative to zinc oxide eugenol wound dressings.